FRI0560 EFFICACY AND SAFETY OF ANAKINRA IN SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS – DATA OF THE BIKER REGISTRY. (June 2019) - Klein, Ariane; Atemnkeng, Veronika Ntam; Dressler, Frank; Foeldvari, Ivan; Küster, Rolf Michael; Hospach, Toni; Ganser, Gerd; Minden, Kirsten; Foell, Dirk; Weller-Heinemann, Frank; Kuemmerle-Deschner, Jasmin; Huegle, Boris; et al.
Abstract : Background: Anakinra (ANA) is recommended for treatment of systemic juvenile idiopathic arthritis (sJIA) and has recently received EMA approval. Objectives: To describe safety and effectiveness of ANA in clinical practice in sJIA patients documented in the German Biologics registry (BiKeR). Methods: Demographic and clinical parameters of the patients were recorded at BiKeR enrollment, ANA effectiveness was evaluated by half-yearly evaluation of disease activity using JADAS-10. Safety assessments were based on MedDRA-coded adverse events (AE) reports. Results: Until December 1 2018, 50 sJIA patients treated with ANA were registered, representing 113.4 patient-years (PY) of observation, with 10 patients (20%) receiving ANA for at least 4 years. The cohort treated with ANA had experienced a prior disease duration of 3.5+/-3.8 years (mean+/-SD). Most sJIA patients treated with ANA received pretreatment: 35 patients (70%) were pretreated with at least one other biologic, mostly etanercept (n=28), followed by tocilizumab (6) and canakinumab (1). Further pretreatments included methotrexate (MTX, n= 35), ciclosporine A (n=13), azathioprine (n=8) and other DMARDs at lower frequency. 39 patients had received corticosteroids. Concomitant treatment consisted of NSAIDs (n=20), systemic steroids (n=35), MTX (n=29) and other DMARDs (n=8). At month 3, JADAS minimal disease activity (MDA)/JADAS remission and inactive disease according to Wallace [1] were observed in 42%/37%and 47%, respectively. After one year of treatment, the rates were 62%/45% and 56%, respectively (Figure 1 ). Conclusion: The current analysis adds to the established safety profile of Anakinra and demonstrates that in ANA treated patients with sJIA the rate of SAEs was comparable and consistent with the overall AE profile of ANA in pediatric patients. Hospitalisation was the usual reason for classification as serious AE. No new safety signals specific to the paediatric population were identified in this large cohort of JIA patients. Disclosure of Interests: Ariane Klein: None declared, Veronika Ntam Atemnkeng: None declared, Frank Dressler Paid instructor for: Abbvie, Pfizer, Novartis, Ivan Foeldvari Consultant for: Chugai, Novartis, Rolf Michael Küster: None declared, Toni Hospach Speakers bureau: Chugai, Roche, Novartis, Gerd Ganser: None declared, Kirsten Minden Consultant for: AbbVie, Dirk Foell Grant/research support from: not specified, Consultant for: not specified, Speakers bureau: not specified, Frank Weller-Heinemann: None declared, Jasmin Kuemmerle-Deschner Grant/research support from: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Consultant for: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Speakers bureau: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Boris Huegle: None declared, Christoph Rietschel: None declared, Eggert Lilienthal: None declared, Gerd Horneff: None declared